DRESS Syndrome Following Anti-Tubercular Therapy: A Case Report - Bam, Niraj; Pokhrel, Milan; Shrestha, Bibek; Yadav, Kundan Kumar; Pandit, Safalta (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Drug Reaction with Eosinophilia and Systemic Symptoms syndrome is a rare, severe cutaneous adverse reaction characterized by widespread rash, fever, hematologic abnormalities, and potential multi-organ involvement. It is most often associated with anticonvulsants, sulfonamides, and allopurinol, while anti-tubercular drugs are rarely implicated. We report the case of a 66-year-old female with a history of tuberculous pericardial effusion who developed recurrent diffuse erythematous, non-blanchable maculopapular rashes with facial edema and systemic symptoms following re-exposure to anti-tubercular therapy. Her symptoms were temporally related to ATT administration, strongly supporting a diagnosis of ATT-induced DRESS syndrome. The patient’s past medical history included hypothyroidism and cerebrovascular accident, but no significant drug allergies. Clinical evaluation revealed fever, facial swelling, generalized pruritic rash, and systemic complaints without significant abnormalities on chest or abdominal examination. Prompt discontinuation of ATT and supportive management led to clinical improvement. This case underscores the importance of early recognition of DRESS, even with uncommon culprits such as anti-tubercular drugs. Given the global prevalence of tuberculosis, ATT-induced DRESS poses unique therapeutic challenges, particularly in balancing drug hypersensitivity management with effective tuberculosis treatment. Clinician awareness and timely intervention remain key to improving outcomes in this potentially life-threatening condition.